Diagnostic and therapeutic radioisotopes in nuclear medicine: Determination of gamma-ray transmission factors and safety competencies of high-dense and transparent glassy shields - Erdemir Rabiye Uslu; Kilic Gokhan; Sen Baykal Duygu; ALMisned Ghada; Issa Shams A. M.; Zakaly Hesham M. H.; Ene Antoaneta; Tekin Huseyin Ozan (Open Chemistry, 2022)
We present the findings of an extensive examination on newly designed CdO-rich and transparent glass shields for nuclear medicine facilities in lieu of traditional and unfavorable materials, such as lead and concrete. Gamma-ray transmission factors of newly designed glass shields are determined using a variety of diagnostic, therapeutic, and research radioisotopes, including 67Ga, 57Co, 111In, 201Tl, 99mTc, 51Cr, 131I, 58Co, 137Cs, 133Ba, and 60Co. A general-purpose Monte Carlo code MCNPX (version 2.7.0) is used to determine the attenuation parameters of different material thicknesses. Next, the findings are compared using a standard concrete shielding material. The results indicate that adding more CdO to the glass composition improves the overall gamma-ray attenuation properties. As a result, among the heavy and transparent glasses developed, the C40 sample containing 40% CdO exhibited the best gamma-ray absorption properties against all radioisotopes. Furthermore, the gamma-ray absorption characteristics of this created high-density glass were shown to be better to those of a standard and heavy concrete sample. It can be concluded that the newly developed CdO-rich and transparent glass sample may be used in medical radiation fields where the radioisotopes examined are used in daily clinical and research applications.